What predicts survival in glioblastoma? A population-based study of changes in clinical management and outcome - Fekete, B.; Werlenius, K.; Tisell, M.; Pivodic, A.; Smits, A.; Jakola, A. S.; Rydenhag, B. (Frontiers in Surgery, 2023)
Background. Glioblastoma is the most common and most aggressive primary brain tumor in adults. Despite multimodal treatment, the median survival time is 15-16 months and 5-year survival rate 5-10%. The primary goal of this study was to identify prognostic factors for survival in an unselected population of patients operated for glioblastoma. The secondary goal was to explore changes in outcome and the clinical management of this patient group over time. Methods. We identified 222 consecutive adults operated for glioblastoma between November 2012 and June 2016 at the Department of Neurosurgery, Sahlgrenska University Hospital in Gothenburg, serving a health care region in the western part of Sweden with 1.900.000 inhabitants. Clinical variables were identified and tested as predictors for prognosis in extended Poisson regression models. The results were compared with a previously published cohort from 2004-2008, before current standard of care based on molecular tumor diagnosis was fully implemented. Results. Median overall survival was 1.07 years, which was significantly longer than in the 2004-2008 cohort (1.07 vs. 0.73 y, age-and sex adjusted HR = 1.89, p < 0.0001). Variables associated with longer survival in the multivariable model were MGMT promoter hypermethylation, non-central tumor location, complete resection of enhancing tumor, WHO performance status 0-1, unilateral tumor location, fewer lobes involved, younger age and no comorbidities. This is a provisional file, not the final typeset article Conclusion. The median survival for patients with glioblastoma treated according to current standard treatment has moderately but significantly increased, with MGMT promoter hypermethylation as the strongest predictor for survival.